Oxidative Stress in the Newborn Period: Useful Biomarkers in the Clinical Setting - Iván Millán; José David Piñero-Ramos; Inmaculada Lara; Anna Parra-Llorca; Isabel Torres-Cuevas; Máximo Vento (MDPI AG, 2018)
Aerobic metabolism is highly efficient in providing energy for multicellular organisms. However, even under physiological conditions, an incomplete reduction of oxygen produces reactive oxygen species and, subsequently, oxidative stress. Some of these chemical species are highly reactive free radicals capable of causing functional and structural damage to cell components (protein, lipids, or nucleotides). Oxygen is the most used drug in ill-adapted patients during the newborn period. The use of oxygen may cause oxidative stress-related diseases that increase mortality and cause morbidity with adverse long-term outcomes. Conditions such as prematurity or birth asphyxia are frequently treated with oxygen supplementation. Both pathophysiological situations of hypoxia⁻reoxygenation in asphyxia and hyperoxia in premature infants cause a burst of reactive oxygen species and oxidative stress. Recently developed analytical assays using mass spectrometry have allowed us to determine highly specific biomarkers with minimal samples. The detection of these metabolites will help improve the diagnosis, evolution, and response to therapy in oxidative stress-related conditions during the newborn period.